Confessions of a Murder Suspect - Patterson, James 1947-; Paetro, Maxine (New York : Little, Brown and Co., 2012)
Tandy Angel is, along with her brothers, a suspect in their parents' murder but having grown up under Malcolm and Maud Angel's perfectionist demands, Tandy decides she must clear the family name no matter what.
Keywords: Siblings -- Fiction; Twins -- Fiction; Perfectionism (Personality trait) -- Fiction; Family life -- Fiction -- New York (N.Y.); Secrecy -- Fiction; Death -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction